Absolute Pediatric Neurology Essential Questions and Answers - Awaad, Yasser M. (Springer International Publishing, 2018)
This practical book features more than 1000 questions and answers with illustrations for pediatric neurologists, adult neurologists, general pediatricians and students taking their initial board examination and maintenance of certification. All questions are in multiple choice format and followed by the correct answer with a full explanation and appropriate references. Chapters are sectioned by different topics in pediatric neurology, including Epilepsy, Metabolic Disorders and Movement Disorders and other topics. Timely and thorough, this is a handy and succinct resource.